Sasak Marong Art As A Tourist Attraction for The Development of A Tourism Village Based on The Distinctive Culture - ., Hariono; ., Budiman; ., Jumaidin (Jurnal Manajemen Pelayanan Hotel, 2024)
This research is motivated by the author's attention related to Sasak art as a tourist attraction located inMarong Village, East Praya District, Central Lombok Regency. The focus of the research studied in this thesisare: (1) How does Sasak Marong art function as a tourist attraction based on the distinctive culture of the SasakLombok Tribe (2) What is the role of the government and the community towards Sasak Marong art as a touristattraction for the development of a typical Sasak Lombok cultural tourism village in Marong Village, East PrayaDistrict, Central Lombok?.This type of research uses descriptive qualitative research. The data collection methods used are: observation,interviews, and documentation. This is done to facilitate researchers in obtaining and compiling the dataneeded. The results of this study indicate (1) the function of Sasak Marong art as a tourist attraction has threefunctions in general, mamely: the function of art as a ritual, the function of art as an expression, and the functionof art as a tourist attraction. Apart from that, there are two main functions of Marong Sasak ert : practicalfunction and aestheatic function. Both of these functions are supporting as a tourist attraction. (2) Thegovernment is the founder, provider and supporter while the community promotes, manages and developsSasak art in Marong Village.Keywords: Art, Tourism Attraction, Village Development, Sasak Tribe Culture